Humanity-Based Leadership Model in the Government of South Sulawesi Province (Integration of Modern Leadership with Local Wisdom) - Ramli, Muhammad; Saleh, Sadhriany Pertiwi (Universitas Islam Negeri Alauddin Makassar, 2020)
This study aims to analyze a collaborative model of modern leadership, namely innovative, transformative and credible with local wisdom by four ethnic cultures, namely Bugis, Makassar, Toraja and Mandar, which in turn will produce officers who prioritize human values in implementing policies based on local wisdom with the philosophy of acca, acca, warani, malempu, and getteng. This research uses qualitative research methods so that the discussion is descriptive. The research was conducted at the South Sulawesi Government Office with four city districts. The research results show that in real terms the human-based leadership model of the Provincial Government of South Sulawesi in its work to improve the welfare of the community with innovative programs and humane services towards advanced governance as the translation of change shows a pretty good trend. Leadership innovation in making change by prioritizing integrity, motivator, ability, experience, honesty, obedience, persistence and intellectuality as a manifestation of the integration of modern leadership and local wisdom as a filter in change so as to lead to an advanced government while still upholding the value of local wisdom as a support which is summarized in Cultured South Sulawesi. Supporting factors that are quite helpful related to the program strategy include the readiness of the apparatus, community involvement and the level of community acceptance, while the inhibiting factors are infrastructure readiness, availability of funds and community readiness to change, but concrete efforts can gradually be overcome so that the strategic program of the South Sulawesi Government as the growth center of the eastern region and the national economic buffer can be realized.